If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15x + -20 = -14x + 40 Reorder the terms: -20 + -15x = -14x + 40 Reorder the terms: -20 + -15x = 40 + -14x Solving -20 + -15x = 40 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. -20 + -15x + 14x = 40 + -14x + 14x Combine like terms: -15x + 14x = -1x -20 + -1x = 40 + -14x + 14x Combine like terms: -14x + 14x = 0 -20 + -1x = 40 + 0 -20 + -1x = 40 Add '20' to each side of the equation. -20 + 20 + -1x = 40 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = 40 + 20 -1x = 40 + 20 Combine like terms: 40 + 20 = 60 -1x = 60 Divide each side by '-1'. x = -60 Simplifying x = -60
| w-0.79=7.47 | | -5+3x-2= | | w-0.79= | | -5= | | -6x-4=44 | | o-6x-4=44 | | -z=6 | | y(2y-8)(2y+6)=0 | | 7x-6=-55 | | -2(2y-8)+10= | | -4t^2+24t+13=0 | | -10-2x=-10 | | 2-3x=-19 | | 7x(3x-8)=0 | | -13+6=m-8 | | -11=6-2n-5 | | 2(4e)= | | z-5z= | | 6(6y-3)=18y | | 4a+2(-2+a)+(-1-a-(-2+a))=11 | | 3(5x+1)+5(x-3)= | | 2d-8=2 | | n^2-10n=-21 | | 4a+2(-2+a)+(-1-a-2+a)=-11 | | 9x^2+36x+34=0 | | 12(6a)= | | 3x(x+2)=3(x^2-2) | | -6(12y)= | | (x(x))-y= | | 2x^3+7x^2=15x | | x+20+3x=19-3x-24 | | -5+9=17x-3-16x |